Notes on the genus Callitriche (Plantaginaceae) in South Africa - Lansdown, Richard V.; Glen, Rene; Hassemer, Gustavo (Phytotaxa, 2017)
Historically there has been confusion over the status and identification of Callitriche species in South Africa. Review of herbarium specimens and fieldwork have enabled confirmation of the presence of C. deflexa as a naturalised species in this country and confirmed that C. compressa and specimens named as C. bolusii are conspecific. Field surveys showed that C. compressa still occurs in the areas from which most historic collections were made with no evidence of a decline, it is widespread but local in Kwa-Zulu Natal and Eastern Cape Provinces and extends into eastern Western Cape Province. However because it is known from only five widely scattered sites, it is classed as Vulnerable under the IUCN Red List. We also typify here the names C. compressa and C. deflexa.